2-[18F]Fluorophenylalanine: Synthesis by Nucleophilic 18F-Fluorination and Preliminary Biological Evaluation - Modemann, Daniel J.; Zlatopolskiy, Boris D.; Urusova, Elizaveta A.; Zischler, Johannes; Craig, Austin; Ermert, Johannes; Guliyev, Mehrab; Endepols, Heike; Neumaier, Bernd (Synthesis, 2019)
2-[18F]Fluorophenylalanine (2-[18F]FPhe), a promising PET tracer for imaging of cerebral infarction and tumors, was efficiently prepared from an easily accessible iodonium salt precursor using Cu-mediated radiofluorination under ‘low base’ or ‘minimalist’ conditions. Whereas significant racemization was initially observed if the ‘minimalist’ protocol was applied for radiolabeling, it was completely suppressed by the careful adjustment of 18F– preprocessing. The initial biological study revealed a higher uptake of 2-[18F]FPhe in different tumor cells in comparison to that of [18F]FET. In contrast to 4-[18F]FPhe, which suffered from rapid defluorination in vivo, 2-[18F]FPhe demonstrated a sufficient in vivo stability. Conclusively, 2-[18F]FPhe is a promising PET probe that is now readily available using Cu-mediated radiofluorination under ‘minimalist’ or ‘low base’ conditions. The simplicity of the translation of the proposed procedures to automated synthesis modules allows a broad biological evaluation of 2-[18F]FPhe. Notably, a novel protocol for the preparation of N-Boc protected amino acids from the respective Ni-Schiff base complexes was developed that avoided application of strongly acidic conditions.
Keywords: amino acids tracer; fluorine-18; positron emission tomography; radiolabeling